Thermal Oxidation of Cold Sprayed Titanium-Based Coating Deposited on Co-Cr Alloy - Cetiner, Dogukan; Paksoy, A. Hilmi; Tazegul, Onur; Baydogan, Murat; Guleryuz, Hasan; Cimenoglu, Huseyin; Atar, Erdem (Springer, 2018)
This study focuses on the surface modification of a medical grade Co-Cr alloy via combining cold spray and thermal oxidation processes. After deposition of a Ti96-Al4 (wt.%) coating, samples were oxidized at 600 degrees C for 60h in air. Oxidation transformed the coating into a dual-layered structure comprising an outer oxide layer (mainly rutile) with a diffusion layer (mainly oxygen enriched titanium and Ti-Al intermetallics) beneath it. Formation of new phases made the diffusion layer brittle and prone to fracture during pull out tests. Scratch and Rockwell-C tests confirmed good adhesion between the oxide and underlying diffusion layers, having average hardness as 1297 HV and 387 HV, respectively. The dual-layer coating exhibited excellent wear performance in a 0.9wt.% NaCl solution against sliding action of alumina ball as compared to Co-Cr substrate, especially at contact pressures<1200MPa, while the maximum in vivo contact pressure is<15MPa for load-bearing orthopedic implants. Furthermore, the release of the aluminum from the dual-layer coating into 0.9wt.% NaCl solution is lower than the permissible limit stated by the International Agency for Research on Cancer.
Keywords: coating; Co-Cr alloy; cold spray; thermal oxidation; titanium; wear